Один из нас: повесть / В. П. Росляков - Росляков Василий Петрович (Современник, 1985)
Экземпляры: абонемент (20210203) / Инвентарный номер: 13625 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Р 75 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6